Tannic acid reduced apparent protein digestibility and induced oxidative stress and inflammatory response without altering growth performance and ruminal microbiota diversity of Xiangdong black goats - Wang, Zuo; Yin, Lei; Liu, Lei; Lan, Xinyi; He, Jianhua; Wan, Fachun; Shen, Weijun; Tang, Shaoxun; Tan, Zhiliang; Yang, Yanming (Frontiers in Veterinary Science, 2022)
The present study was performed to evaluate the impacts of tannic acid (TA) supplementation at different levels on the growth performance, physiological, oxidative and immunological metrics, and ruminal microflora of Xiangdong black goats. Twenty-four goats were randomly assigned to four dietary treatments: the control (CON, basal diet), the low-dose TA group [TAL, 0.3 % of dry matter (DM)], the mid-dose TA group (TAM, 0.6 % of DM), and the high-dose TA group (TAH, 0.9 % of DM). Results showed that the growth performance was unaffected (P > 0.05) by adding TA, whilst the 0.3 % and 0.6 % TA supplementation significantly decreased (P < 0.05) the apparent digestibility of crude protein (CP) and ruminal NH3-N concentration, and raised (P < 0.05) the level of total volatile fatty acid (TVFA) in rumen. The increments of alanine aminotransferase (ALT), triglyceride (TG), cortisol (CORT), total antioxidant capacity (T-AOC), interleukin (IL)-1β, IL-6, and serumamyloid A (SAA), and decrements of globulin (GLB), immunoglobulin G (IgG), cholinesterase (CHE), glutathione reductase (GR), creatinine (CRE), growth hormone (GH), high-density lipoprotein cholesterol (HDLC), and insulin-like growth factor 1 (IGF-1) to different extents by TA addition were observed. Although the Alpha and Beta diversity of rumen bacterial community remained unchanged by supplementing TA, the relative abundance of the predominant genus Prevotella_1 was significantly enriched (P < 0.05) in TAL. It could hence be concluded that the TA supplementation in the present trial generally decreased CP digestion and caused oxidative stress and inflammatory response without influencing growth performance and ruminal microbiota diversity. More research is needed to explore the premium dosage and mechanisms of effects for TA addition in the diet of goats.